Antimicrobial Effect of Lactobacillus as a Probiotic Isolated from Yoghurt Products Against Staphylococcus aureus and Escherichia.coli - Khalil, Israa Ibrahim; Fadihl, Suhail Jawdat; Ali, Haifaa Hussain (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Probiotic bacteria using in commercially produced foods are at most members of the genera Lactobacillus and Bifidobacterium. This research was aimed to study the antimicrobial effect of lactobacillus bacteria as probiotic against some pathogenic bacteria, strains of lactobacillus bacteria were isolated from two types of yoghurt in Baquba city, Iraq . Total of 60 yoghurt samples from 2 origins (30 locally and 30 commercial produced yoghurt) were used to isolate probiotic bacteria which were identified phenotypically and biochemically. 30 (100%) of locally produced yoghurt samples include with probiotic bacteria while 12 (40%) commercially types of yoghurt samples were contained with probiotic, the method of modified agar overlay was used to determine the antibacterial activity among the lactobacillus isolates. Results indicated spectrum of their antibacterial effects which were varied against the selected pathogenic bacterial isolates (Staphylococcus aureus and Escherichia.coli ). The results of this study encourage people to consume more probiotic dairy products instead of using antibiotic drugs as prophylactics which lead to health problems also encourage local industry for producing bioyoghurt products.